If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4u + 2(u + -5) = -28 Reorder the terms: -4u + 2(-5 + u) = -28 -4u + (-5 * 2 + u * 2) = -28 -4u + (-10 + 2u) = -28 Reorder the terms: -10 + -4u + 2u = -28 Combine like terms: -4u + 2u = -2u -10 + -2u = -28 Solving -10 + -2u = -28 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -2u = -28 + 10 Combine like terms: -10 + 10 = 0 0 + -2u = -28 + 10 -2u = -28 + 10 Combine like terms: -28 + 10 = -18 -2u = -18 Divide each side by '-2'. u = 9 Simplifying u = 9
| x/2-2=11 | | 12(-12x+6)=25(x-2) | | 9/10x=9/11 | | -6+3y=-3+6y | | 20(6x+7)=-5(x-5) | | 9b+8=-8-7b | | -6x+5=3+5x | | 9(3x-23)=1(x+5) | | -4-4c=6-2c | | 4x^3-12x^2-4X=0 | | 5e^2x-1-3=12 | | 8q-5=9q | | 1.9=9.1-0.9x | | -3(2b-5)=2b | | 19(3x-6)=25(x+2) | | -9h=-10h+10 | | 4r^2-16r-128= | | 125=8-3x | | 1.9=1.9-0.9x | | x/7-5=-11 | | -6m=-8-8m | | 6x+3x-5=49 | | -8r=10+2r | | 12x-20y=12 | | (2+3i)(x-iy)=3(x-2iy)+(2+i) | | -5+8x=2(14x+10)-x | | v+7=v | | -12x+7=-5 | | 9j-10=8j | | 14x+28-10x=8 | | (v^7)(v^2)= | | Tanx=0.44469726 |